THE MODERATOR EFFECT OF FINANCIAL APPS ON THE RELATIONSHIP BETWEEN FINANCIAL EDUCATION AND FINANCIAL CAPABILITY - Nanik Linawati; Inlian Wijaya (Finance and Investment Program, School of Business and Management - Petra Christian University, 2022)
This study aims to determine the effect of Socio-Demographic and Financial Education on Financial Capability with Financial Apps as the moderator variable. The research population is Generation Z aged 19-26 years. The research sample amounted to 100 respondents and data collection was done through the distribution of questionnaires via google form. The data analysis method used is Partial Least Square (PLS). In the industrial era 4.0, which is growing rapidly at this time, financial applications that are designed to help people manage finances have begun to appear. Digital financial management applications make people manage personal finances easily and practically. Financial management applications encourage people to further upgrade their knowledge about financial management to achieve financial goals in the future. The results showed that gender had a significant effect on financial capability and financial apps played a role in moderating the influence of gender on financial capability.